Women and Leadership: How Do Women Leaders Contribute to Companies' Sustainable Choices? - Pierli, Giada; Murmura, Federica; Palazzi, Federica (Frontiers in Sustainability, 2022)
The current political, economic and social scenario is characterized by continuous and rapid changes. Companies are therefore called to face a significant change, which requires the definition of policies and strategies strongly oriented towards sustainable development, becoming fundamental for long-term success and competitiveness. In this perspective, female leadership plays a key role. Over time, women have demonstrated the ability to successfully manage the challenges imposed by social dynamics and environmental change. Despite the growing number of studies on women as sustainable development leaders, there is still little empirical evidence on how women contribute to the to the companies’ sustainable development. The paper aims to address this gap by developing a qualitative multiple case study based on the administration of questionnaires to five Italian companies characterized by the presence of women in leadership positions. Therefore, the objectives of the research work are: (i) to analyze how female leadership facilitates the company's transition towards sustainability; (ii) to define a "typical profile” of sustainable woman leader in terms of main characteristics, actions and challenges. Findings suggest that female leadership contributes to the promotion and implementation of environmental and social practices through several characteristics intrinsic to their nature, such as the ability to emphasize and listen and the predisposition to sharing and collaboration. In addition, sustainable women leaders exhibit the following main traits: thinking systematically/holistically, managing complexity, and inclusive approach to leadership. This study allows to enrich the literature related to the relationship between sustainability and female leadership, providing empirical evidence on the topic.